The wild species of Phaseolus (Fabaceae) in Nuevo León, Mexico - Acosta-Díaz, Efraín; Hernández-Torres, Ismael; Amador-Ramírez, Mario Domingo; Padilla-Ramírez, José Saúl; Zavala-García, Francisco (Revista Mexicana de Ciencias Agrícolas, 2018)
The Sierra Madre Oriental region, although known for its diversity of wild species of the genus Phaseolus (Fabaceae) has been partially and not always systematically explored, moreover, in the INIFAP germplasm bank there are no seed samples for characterization and ex situ conservation. Based on the above and the increasing reduction of genetic variability by anthropocentric causes, it was decided to carry out exploration and collection of wild species of Phaseolus. The aim of this study was to document the collection of wild bean populations in the Sierra Madre Oriental region in Nuevo León. Between 2010 and 2012 an intense exploration was carried out in 12 municipalities of Nuevo León. Seven species were located and identified (Phaseolus neglectus, P. leptostachyus, P. pedicellatus, P. albiflorus, P. novoleonensis, P. maculatifolius and P. zimapanensis) and 54 seed samples were collected, most came from the Santiago (20%), Aramberri (19%) and Rayones (15%) municipalities; while 46% was obtained in other municipalities. The collected germplasm was ex situ preserved in the germplasm bank of the Antonio Narro Autonomous Agricultural University. However, previously reported species are likely to be lost over the years, therefore there is a need to continue the collections in Nuevo León, and other states in the region.
Keywords: Phaseolus spp.; wild species; genetic resources; Nuevo León